"Audit – sources and institutionalization” By Evgeniy Nikolov Stoyanov - Terziev, Venelin (Journal of Economic Development, Environment and People, 2015)
The author of the presented book (published in the form of a monograph)is a professor in economics with PhD in accounting, control and analysis of economic activity. He is a lecturer in: Burgas University "Asen Zlatarov", Agricultural University - Plovdiv and University of agribusiness and rural development - Bulgaria. His scientific research is in the field of audit and its application in various areas which is reflected in over 60 publications in Bulgaria and abroad. Prof. Evgeniy Stoyanov is one of the prominent Bulgarian scientists in that field having original ideas in his work presented on a number of conferences, seminars and scientific forums. The monograph “Audit – sources and institutionalization” consists of an introduction, eight chapters, conclusion, references and a glossary of abbreviations used. It will be shortly presented and analyzed below as a book of special interest in the development of scientific thought in economics and management.